Perbandingan Kinerja Reksadana Syariah dan Pasar JII Menggunakan Metode Treynor (Studi Kasus Reksadana Saham Syariah, Reksadana Syariah Pendapatan Tetap dan Reksadana Syariah Pendapatan Campuran Periode 2011-2015) - Sarah Aulia Rahma; Ari Prasetyo (Universitas Airlangga, 2017)
This research aims to find out the comparison between the performance of Islamic mutual funds of stock, Islamic mutual funds of fixed income and combined Islamic mutual funds with the market (Jakarta Islamic Index) as benchmark by using Treynor method. The method of this measuring calculates upon the risk factors and the return rate of those three kinds of Islamic mutual fund and benchmark. This research uses 21 samples of Islamic mutual fund in Indonesia which consist of seven Islamic mutual funds of stock, seven Islamic mutual funds of fixed income and seven combined Islamic mutual. The approach used is a quantitative approach with the analysis technique of ANOVA. The result of this study shows that there is no difference between the performances of Islamic mutual funds of stock, Islamic mutual funds of fixed income, combined Islamic mutual funds and the market onperiod of January 2011 until December 2015.